(untitled) (International Journal of Engineering and Computer Science, 2017)
As in the competitive environment, it becomes necessary to focus on retaining churn customers as well as attracting new customers. Various algorithms of Data Mining have been used for making distinguish between customers into loyal and churn. This paper represents the ant bee colony algorithm which has been used to get accurate results. The use of ABC with two best values local best and global best makes it more effective to obtain the more pleasing and comfortable results. PSO is used to search the best solution with two best values named pbst and gbst by using iteration with initial velocity and positions.